Analisis kompetensi penguasaan aplikasi pembelajaran matematika dan teknologi pembelajaran pada mahasiswa prodi pendidikan matematika FKIP - Gultom, Sanggam P.; Sinaga, Samuel Juliardi; Sauduran, Golda N. (IKIP Siliwangi, 2025)
This study aims to analyze the competence of mastering mathematics learning applications and learning technology in students of the Mathematics Education Study Program. This study uses a descriptive quantitative approach to evaluate the level of mastery of students and lecturers of various applications and learning technologies that are relevant in the context of mathematics education. Data were obtained through questionnaires and analyzed descriptively. The results of the study indicate that competence in mastering mathematics learning applications and technologies, both in lecturers and students, is still not optimal. However, respondents' perceptions emphasize the importance of this ability to support the effectiveness of the learning process. Respondents' perceptions indicate that mastery of mathematics learning applications, such as geogebra, mathway, photomath, as well as e-learning platforms and artificial intelligence, is an urgent need to improve teaching effectiveness. This indicates the need to develop specific strategies, both in the form of improving skills in mastering learning applications and technologies, or in the form of deeper technology integration in the mathematics education curriculum